Association between child sexual abuse and infectious disease diagnoses. (November 2019) - Dargan, Sonia; Daigneault, Isabelle; Ovetchkine, Philippe; Jud, Andreas; Frappier, Jean-Yves
Abstract: Background: Though many studies have linked child sexual abuse (CSA) to psychological health problems, little is known regarding the relationship between CSA and children and adolescents' physical health. Objective: The objective of this study was to assess the relationship between CSA and infectious disease diagnoses. Participants: Of the 955 eligible children and adolescents who had a substantiated report of sexual abuse between 2001 and 2010, medical data was retrieved for 882 individuals, who formed the sexually abused group. These 882 participants were matched to 882 participants on age, gender, and administrative healthcare region to form the general population group. Setting and methods: This matched-cohort study, conducted in a large Canadian city, compared the number of infectious disease diagnoses between the date of the substantiated sexual abuse report and August 1, 2013, between the two groups. Results: Results indicate that sexually abused participants had 1.27 times more (95% CI – 1.13 to 1.42) infectious diseases diagnoses than those from the general population. They received 1.83 times more genitourinary infection diagnoses (95% CI – 1.43 to 2.33), 1.31 times more diagnoses for other types of infections (95% CI – 1.11 to 1.55) and 1.21 times more respiratory and ear infection diagnoses (95% CI – 1.05 to 1.40). There was no statistically significant difference regarding skin infection diagnoses. These results indicate an association between CSA and more frequent infectious diseases diagnoses.